THE ROLE OF SERVICE QUALITY, BRAND IMAGE, AND WORD OF MOUTH ON COLLEGE DECISIONS WITH CONSUMER SATISFACTION AS INTERVENING VARIABLES (STUDY ON RPL PROGRAM AT IIB DARMAJAYA) - Dian Eka Darma Wahyuni; Hakim, Lukmanul; Ma'ruf, M. Hasan Ma'ruf (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of service quality, brand image, and word of mouth on the decision to continue studying, with consumer satisfaction as an intervening variable in the context of the Past Learning Recognition Program (RPL) at the Darmajaya Institute of Informatics and Business (IIB Darmajaya). Data were collected from students of the RPL IIB Darmajaya Program using the purposive sampling, with a total of 100 respondents. The analysis was performed using multiple regression with the help of SPSS software. The results of the study show that service quality, brand image, and word of mouth have a significant effect on consumer satisfaction, but only word of mouth has a significant influence on college decisions. Consumer satisfaction is proven to be a significant intervening variable in strengthening the influence of independent variables on college decisions. This research emphasizes the importance of word of mouth strategy and consumer satisfaction in improving the decision of prospective students to continue their education. Higher education institutions such as IIB Darmajaya can capitalize on these findings by improving service quality and building a positive brand image, while encouraging effective interpersonal communication among students and alumni.Keywords: Service Quality, Brand Image, Word of Mouth, Consumer Satisfaction, College Decision, RPL.